The Aspects of Improving the Supply Chain Competitiveness in the Context of Digital Transformations of the Economy - Skitsko Volodymyr I.; Voinikov Mykola Yu. (Bìznes Inform, 2023)
The article considers the issue of competitiveness of supply chains in the context of digital transformations and constant economic changes. The interpretation of the concept of competitiveness may differ depending on the object under study, therefore, in addition to the general definition of the concept of «competitiveness», an analysis of the concept of competitiveness of supply chains and competitiveness of the supply chain link in the contemporary literature is carried out and an own generalized definition of the concept is presented. Methods for determining the level of competitiveness used to assess the level of competitiveness of a product or enterprise are not always applicable to supply chains because of the specifics of their operation. The publication presents possible qualitative and quantitative methods for determining the level of competitiveness, such as: points method, rank method, integral assessment method, SWOT-analysis, heuristic methods, and others. Some of the methods, including the points method and SWOT analysis, have been adapted for supply chains and demonstrated in practical application using conditional examples for visibility. The characteristics influencing the competitiveness of the supply chain, in particular flexibility, reliability, efficiency, integration, have been allocated. Possible ways to improve these characteristics are provided. It is determined that improving the level of competitiveness of an individual link in the supply chain leads to an improvement in the level of competitiveness of the entire supply chain, and while improving the level of competitiveness of several links in the supply chain, a synergy effect can be observed in the context of competitiveness. In terms of competitiveness of the supply chain, it is appropriate to take into account the specifics of the functioning of the participant in the supply chain, its business processes, the number of incoming and outgoing material flows and flows of information. The article analyzes the last link in the supply chain – the last-mile logistics in e-commerce, which is gaining momentum in Ukraine, owing not least to the COVID-19 pandemic and the full-scale russian invasion in 2022. Ways to improve the level of competitiveness of the last link in the supply chain on the example of e-commerce are proposed.